2013
DOI: 10.4161/epi.24947
|View full text |Cite
|
Sign up to set email alerts
|

ANGPT2promoter methylation is strongly associated with gene expression and prognosis in chronic lymphocytic leukemia

Abstract: (2013) ANGPT2 promoter methylation is strongly associated with gene expression and prognosis in chronic lymphocytic leukemia, Epigenetics, 8:7,[720][721][722][723][724][725][726][727][728][729]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…CLL patients may have a negative impact on their disease course with a notable increase of Ang-2 ligand expression (97), which is accompanied with an aberrant vascularization in (bone marrow) BM sections (98). Recent epigenetic evidence showed that Ang-2 displays lower DNA methylation in CLL and correlates with poor prognosis and shorter survival (97). Additionally, Binet staging can be linked to elevated levels of Ang-2 (93).…”
Section: Angiogenin (Ang) Family Related To Leukemogenesismentioning
confidence: 99%
“…CLL patients may have a negative impact on their disease course with a notable increase of Ang-2 ligand expression (97), which is accompanied with an aberrant vascularization in (bone marrow) BM sections (98). Recent epigenetic evidence showed that Ang-2 displays lower DNA methylation in CLL and correlates with poor prognosis and shorter survival (97). Additionally, Binet staging can be linked to elevated levels of Ang-2 (93).…”
Section: Angiogenin (Ang) Family Related To Leukemogenesismentioning
confidence: 99%
“…Since CLL patients display lower Ang1 level, we could infer that accessory cells in the CLL microenvironment, which normally secrete Ang1 and maintain quiescent Ang-Tie2 signalling, or CLL themselves, have lost their Ang1 secretion ability. Since increased expression of Ang2 [28] is associated with changes in the Ang2 promoter methylation pattern [8], a similar scenario could explain the lower Ang1 levels detected in CLL samples. Further research is necessary to identify the specific cell populations with compromised Ang1-expressing capabilities in the CLL microenvironments.…”
Section: Discussionmentioning
confidence: 90%
“…Previously Kay et al analysed the expression of some angiogenic factors and receptors in CLL patients, detecting expression of Tie1 and Ang1 and similarly failed to detect Tie2 transcripts [2]. Ang2 expression in CLL and its correlation with disease progression has been extensively described in the literature [6,8,28]. Furthermore, Aguayo et al described Tie1 expression [29] in CLL samples and its correlation with CLL disease stage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations